The Effect of Inflation on Fund Supply of Participation Banks: An Application to Türkiye with ARDL Approach - Mercan Hatipoğlu; Caner Dilber (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The primary economic variable that threatens price stability is inflation. Since inflation directly affects the quality of life standards of every individual living in a country, it is one of the most important problems for economies. The aim of this study is to investigate the effect of inflation on the fund supply of participation banks. The relationship between the amount of funds offered to the market by participation banks operating in Turkey and the CPI values were analyzed at monthly frequency for the period between of 2012-2022. In order to determine the stationary of the series, the structural break ADF unit root test were used and ARDL were preferred as the estimation model. According to the results of the analysis, inflation affects the fund supply of participation banks negatively in the short term. On the other hand, a positive significant relationship between inflation and participation banks fund supply was found in the long run. All in all in an inflationary environment, the loans offered by the participation banks to the markets follow a U-shaped trend, first decreasing and then increasing and increases in inflation rates threaten the credit growth of participation banks. In addition, we pointed out that it is a necessity to bring inflation rates to a modarate level so that participation banks are not excluded from financial markets in Turkey.